Analysis of green chemistry content in form IV and V high school chemistry textbooks in Malaysia - Aura Heidya Septa; Antuni Wiyarsi (Indonesian Journal of Chemical Education, 2025)
Malaysia is one of the countries that has integrated the STEM (Science, Technology, Engineering, and Mathematics) approach in its education curriculum since 2017, to prepare young people with 21st century skills. In the context of chemistry education, Malaysia also applies the concept of Green Chemistry to encourage environmental awareness and improve science literacy through materials relevant to global sustainability issues. This study examines the integration of Green Chemistry principles in Level IV and V high school chemistry textbooks in Malaysia. Utilizing a qualitative descriptive content analysis, the study focuses on six themes: Green Chemistry principles, application fields, presentation stages, presentation levels, locality aspects, and related chemistry concepts. Analysis of the textbooks revealed that seven out of twelve Green Chemistry principles are integrated, with "Preventing Potential Accidents" appearing most frequently (56.52%), followed by "Waste Prevention" (14.50%). The application fields of Green Chemistry predominantly cover health (50.73%) and environmental issues (28.99%). Presentation stages emphasize content deepening (52.17%) and core materials (21.74%), while presentation levels are largely explicit (52.17%), enhancing conceptual clarity. However, locality aspects are underrepresented, with global contexts dominating (92.75%) over local ones (7.25%). The integration of related chemistry concepts includes "Acid and Base" (26.09%) and "Organic Compounds" (18.84%) as the most frequent. Despite the significant integration of Green Chemistry, the study highlights gaps in contextual representation and recommends future research focus on enhancing the relevance of textbook content to local and global environmental issues.